Revised direct bandgap and band parameters for AlP: hybrid-functional first-principles calculations vs experiment - Cónal Murphy; Eoin P. O’Reilly; Christopher A. Broderick (APL Materials)
Despite its relevance to the development of quantum-confined heterostructures for classical and quantum applications, there is significant uncertainty regarding several key band parameters for the indirect-gap III–V semiconductor AlP. Critically, using hybrid-functional first-principles calculations, we find that the Γ6c–Γ8v bandgap is ∼1 eV larger than the widely assumed value of 3.63 eV. This prediction is validated by using interband transition energies obtained from the hybrid-functional band structure to perform a constrained fit to spectroscopic ellipsometry data from the literature. Having validated the band structure vs experiment, we compute revised band parameters for AlP, including band edge effective masses, interband momentum (Kane) matrix elements, band edge deformation potentials, direct and indirect bandgap pressure coefficients, and natural valence band offset. Band parameters are also calculated using the Tran–Blaha modified Becke–Johnson exchange potential. Our results reconcile the spread in reported bandgaps and the conduction band valley ordering in AlP, while providing a consistent set of revised band parameters—including 8-band k · p parameters—to inform improved understanding of III-P electronic, optical, and transport properties.